Metabolomic profiling identifies metabolites in the pheromone glands of Agriophara rhombata associated with the synthesis and release of female pheromone signals - Hao Qu; Yaqin Long; Long Chen; Ziwen Luo; Hongyun Chen; Xuesong Wang; Lixue Long; Jun Tian; Tingting Jing; Linbo Chen (Heliyon)
The tea moth pest, Agriophara rhombata is an economically important and highly damaging pest that drastically affects tea plant leaves. The chemical composition of its pheromone glands metabolites before and during calling period has not been reported yet. Therefore, the present study aimed at the metabolomic profiling of female moths’ sex pheromones glands before and during calling period using gas chromatography time-of-flight mass spectrometry. A total of 114 significant differentially expressed metabolites were identified including 54 up- and 70 down-regulated metabolites in pheromone glands of the female moth. Two of the important previously recognized moth pheromones were identified including E,Z-5,7-dodecadien-1-ol acetate and Z-12-Octadecen-1-ol acetate, which were downregulated. The top ten up-regulated metabolites were “dodecanamide”, “tetradecanamide”, “2-propyn-1-amine, N,N-dimethyl”, “cyclohexane, (1-methylethyl)”, “tetradecane, 2-methyl”, “1-cyclopentyleicosane”, “cyclohexane, octyl”, “1-decan-3-one”, “cyclopentane, decyl” and “cyclopentadecane”. In conclusion, while most of the identified compounds have not previously been identified as primary pheromones in moths, their differential expression in A. rhombata's pheromone glands during the calling period strongly suggests their supporting roles in the synthesis, stabilization, or release of the active pheromone components.